2017
DOI: 10.21162/pakjas/17.4245
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF MYCORRHIZAE AND ACTINOMYCETES ON GROWTH AND BIOPROTECTION OF Capsicum annuum L. AGAINST Phytophthora capsici

Abstract: To evaluate the inoculation effect of Arbuscular Mycorrhizal Fungi (AMF) and actinomycetes on promoting plant growth and diminishing wilt in pepper plant (Capsicum annuum L.), a pot experiment was conducted under greenhouse conditions using a factorial design on random blocks. It was evaluated the native Cerro del Metate mycorrhizal consortium, and ABV39 and ABV02 actinomycetes were evaluated against the CH11 stain of Phytophthora capsici. Responses of the variables evaluated were plant height, stem diameter, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
(32 reference statements)
0
2
1
Order By: Relevance
“…The percentage of colonization by vesicles was relatively low and excels the mycorrhizal consortium of site 2 with 3.6 %, the lower colonization might be associated to the fact that the plants were evaluated when they were in an active stage of growth; thus, the development and the establishment of mycorrhizal symbiosis was in its early stages. Treatments showed significant statistical differences (Tukey, P ≤ 0.05) in the number of spores, being the consortia of the sites 4 (CS4) and 2 (CS2) the ones with the highest number of spores with 2590 and 2002 spores in 100 g of dry soil, the lowest value was found in site 5 (CS5) with 639 spores in 100 g of dry soil (Table 2); the spores quantified in this study are higher compared to other studies; for example Carballar-Hernández et al (2018) reported between 10 and 310 spores in Poblano pepper plants 90 days after inoculation, Reyes-Tena et al (2016) reported between 130 and 406 spores in the same culture but 56 days after transplantation, subsequently Reyes-Tena et al (2017) reported between 125 and 257 spores in Poblano pepper 86 days after transplantation.…”
Section: Identified Amf Speciescontrasting
confidence: 61%
“…The percentage of colonization by vesicles was relatively low and excels the mycorrhizal consortium of site 2 with 3.6 %, the lower colonization might be associated to the fact that the plants were evaluated when they were in an active stage of growth; thus, the development and the establishment of mycorrhizal symbiosis was in its early stages. Treatments showed significant statistical differences (Tukey, P ≤ 0.05) in the number of spores, being the consortia of the sites 4 (CS4) and 2 (CS2) the ones with the highest number of spores with 2590 and 2002 spores in 100 g of dry soil, the lowest value was found in site 5 (CS5) with 639 spores in 100 g of dry soil (Table 2); the spores quantified in this study are higher compared to other studies; for example Carballar-Hernández et al (2018) reported between 10 and 310 spores in Poblano pepper plants 90 days after inoculation, Reyes-Tena et al (2016) reported between 130 and 406 spores in the same culture but 56 days after transplantation, subsequently Reyes-Tena et al (2017) reported between 125 and 257 spores in Poblano pepper 86 days after transplantation.…”
Section: Identified Amf Speciescontrasting
confidence: 61%
“…Their relationship with biocontrol promoting actinomycetes has been gaining attention in the last years. Reyes-Tena et al (164) tested the synergistic effect of a mycorrhizal consortium with two strains of actinomycetes (ABV39 and ABV02) against Phytophthora capsici in pepper plants (Capsicum annuum L.). The results showed that the co-inoculation of the AMFs with the actinomycetes decreased the disease 3 points on a severity scale.…”
Section: Biocontrol Promoting Actinomycetes As Biopesticidesmentioning
confidence: 99%
“…The protection of plants by AM fungi against a number of soil‐borne pathogens has been confirmed, and mechanisms such as nutritious/infection site competition, root anatomical/architectural alteration, and systemic resistance and mycorrhizosphere regulation have been ascribed (Hu et al, 2010; Wehner et al, 2010; Pozo et al, 2013; Li et al, 2021). The charming antagonistic effects of AM fungi on pepper Phytophthora blight through regulating plant immunity and/or rhizospheric environment have also been demonstrated (Alejo‐Iturvide et al, 2008; Hu et al, 2020; Ozgonen & Erkilic, 2007; Reyes‐Tena et al, 2017).…”
Section: Introductionmentioning
confidence: 96%